Penny for Your Thoughts: Searching for the 50 Cent Party on Sina Weibo - Yang, Xiaofeng; Yang, Qian; Wilson, Christo (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Evidence suggests that the Chinese government employs “Internet Commentators” to post propaganda on social media. This group is pejoratively nicknamed the “50 cent party” or Wumao. In this study, we make the first attempt to quantify the size and behavior of the Wumao. Our study leverages a large corpus of data from Sina Weibo (Twitter in China) that includes 26M tweets and comments from 2.7M users over the span of one year. Unfortunately, detecting the Wumao is difficult because there is no ground truth information about them. To overcome this challenge, we apply a series of unsupervised techniques to filter our dataset and isolate suspicious users who exhibit characteristics indicative of being Wumao.